Advantages and disadvantages of public funding - Radolova, O. (My University, 2019)
Public funding has its advantages and disadvantages. Speaking about advantages of public funding it should be mentioned that public funding often represents the largest amount of money available to fund organizations or initiatives.
Keywords: public funding; funding; budgeting